Interactive learning with probability / Wan Nur Azreen Wan Mohd Saidi - Wan Mohd Saidi, Wan Nur Azreen (2016)
This project is focus on how to develop an interactive content as approach in teaching, ‘Interactive Learning With Probability”. This project use interactive contents its multimedia element to enhance student’s study. Teaching probability using interactive content as technology approach in teaching is suitable ways for helping students in learn concepts of probability in class. One of the problems is current method of the learning not effective enough for students to make decision making in solving problem. Therefore, based on the problem one of the objectives of this project is to develop a interactive content for improve students understanding in learning the concepts. The first methodology that used is an analysis the problem statement by conducted from pre-data collection and interview. Next method is design phase which is the storyboard will be drawn to become a guideline in the next phase. The third method is development, in the development phase, all software and hardware will be used to conduct a project based on the storyboard. The fourth method is implementation phase that will be testing to the students to get an evaluation that will be used in the last phase. In the last phase, the measurement will be measured on the effectiveness of the project based on the testing. In conclusion, the final product of the project has achieved the objective and be able to use the approach for teaching and learning by using computer based learning in created a good content for material learning.